Graphic Design Analysis of the Nickelodeon Animated Film Poster Plankton: The Movie (2025) - Ismoyo, Katrin Nur Nafi’ah (Eduvest - Journal of Universal Studies, 2025)
Science has always evolved, ranging from technical science to creativity. One of the sciences that cultivates creativity is fine art, in this study focuses on fine art (graphic design). This study analyzed the 2025 movie poster "Plankton: The Movie" from Nickelodeon, with the results of the overall analysis, this poster is an example of a successful visual communication design in the context of an animated movie poster. Posters not only attract attention visually but also effectively convey the basic premise of the film, generate curiosity, and build anticipation. Strategic design decisions in typography, color, composition, balance, and focus work in harmony to create a poster that fulfills its marketing goals while staying true to the familiar aesthetic of the SpongeBob SquarePants franchise.